(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2026)
Green innovation is vital for tackling climate change and promoting sustainable development, especially in least developed countries like Nepal, which faces unique socioeconomic and environmental hurdles. Despite commitments under the Nationally Determined Contributions, there is a significant gap between the development and practical implementation of green innovations. This study analyses the factors contributing to this gap and proposes a green growth framework that balances economic, social, and environmental priorities. Employing qualitative methods, the research involved content analysis of semistructured interviews with six experts during the OCEM Second International Conference on Green Technologies and Sustainability for a Sustainable Future. Key findings indicate that the practical application of green innovations is hindered by weak policy enforcement, limited institutional coordination, inadequate financial incentives, and poor linkages among research institutions, educational systems, and industry. Although there is growing awareness of environmental sustainability and increased individual adoption of green practices, systemic barriers such as outdated curricula, lack of technical standards, and insufficient knowledge dissemination impede large-scale implementation. The study also highlights the underutilisation of indigenous knowledge and locally adapted, low-cost solutions as missed opportunities to bolster resilience and sustainability, particularly in rural areas. The findings, informed by political ecology and socio-technical transition theory, suggest that the main challenges stem from structural and governance-related issues rather than technological shortcomings. The study concludes that fostering green growth in Nepal requires integrated policy frameworks, enhanced institutional capacity, inclusive governance, and collaboration among academia, industry, communities, and policymakers to bridge the gap between innovation and practice, thereby supporting equitable and context-sensitive development